SOME IMMUNOMODULATING EFFECTS OF ATORVASTATIN (World Journal of Current Medical and Pharmaceutical Research, 2019)
The present study was conducted to investigate the immune-pharmacological effects of atorvastatin on the cellular and humoral immune response of rabbits (either non-vaccinated or vaccinated with rabbit hemorrhagic viral disease vaccine). Two blood samples were collected from each rabbit (5rabbits /group) at the 1st and 3rd day, 1st, 2nd and 3rd week post vaccination and/or drug administration for studying both cellular and humoral immune response.